CSC307: Introduction to Web Programming / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2018)
This course is designed for beginners to learn the concepts, mechanisms and skills used to create web pages and websites using HTML tools and web editors. Emphasis is given on good page layout from the perspective of commercial website design.